Synergistic Effects of Flower Color and Mechanical Barriers on Pollinator Selection Within the Papilionoideae of Fabaceae - Xiang Zhao; Ruochun Gao; Jie Bai; Jing Rong; Xuexia Wei; Hairong Wang; Xiaojuan Zhu; Kun Sun; Qinzheng Hou (Plants)
Current understanding of synergistic trait effects in plant–pollinator systems remains limited, particularly regarding combined visual and mechanical screening mechanisms. Given the specialized flower opening mechanisms and diverse color signals in the Papilionoideae of Fabaceae, this study examines how floral color and mechanical traits jointly mediate pollinator selection in five co-flowering sympatric species. The flower structure of Papilionoideae typically features a keel formed by fused petal lobes that encloses reproductive organs, with flower operative strength thresholds directly reflecting the mechanical resistance required to dehisce the keel and access nectar/pollen. Flower operative strength thresholds and insect mechanical capabilities were quantified, and visitation behaviors were observed under natural conditions. Significant interspecific variation in flower mechanical strength (12.59–20.25 mN) was identified, with visiting insects consistently exhibiting strengths exceeding these thresholds, suggesting mechanical barriers selectively filter pollinators. Non-visiting insects exhibited either insufficient or excessive strength relative to floral thresholds, which is related to the flower-visiting preferences of different insects. Although no linear correlation was found between flower color (RGB color space) and mechanical strength, the combined analysis revealed synergistic screening where color attracted specific pollinators from a subset capable of overcoming mechanical barriers. These findings demonstrate that flower color and mechanical traits function as complementary filters, optimizing pollinator efficiency and excluding ineffective visitors. The study highlights the necessity to explore multi-trait interactions in plant–pollinator co-evolution, with implications for biodiversity conservation and ecosystem service management.